Effect of integrated use of organic manures and chemical fertilizers on yield, nutrient uptake and nutrient balance in the bush bean - T. Aus - T. Aman cropping patterns (Bangladesh Journal of Agricultural Research, 2010)
A study was made on integrated nutrient management in the Bush bean −T. Aus −T. Arnan cropping pattern over three years at BRRI Farm, Gazipur (AEZ-28) during 2000-02. Different packages of chemical fertilizers in combination with organic materials (cowdung and rice straw/bush bean stover) were evaluated to find out a suitable combination for obtaining higher yield of crops. There was a positive effect of crop residue recycling and residual effect of cowdung on the yield of the next crops. Both the soil test based fertilizer and the cowdung with IPNS basis fertilizer treatments gave higher pod yield of bush bean. For T. Aus rice, the highest yield was obtained with the treatment where bush bean stover was used along with IPNS based chemical fertilizer. Again the highest yield of T. Aman rice was observed in the residual effect of cowdung with reduced amount of fertilizer. An excess N uptake was recorded where N was added as fertilizer only. The apparent balance (nutrient added through manures and fertilizers minus nutrient removed by crops) for both N and K was negative while that for P & K was mostly positive.Key Words: IPNS; cowdung; rice straw; bush bean; rice; nutrient balance. DOI: 10.3329/bjar.v34i1.5765Bangladesh J. Agril. Res. 34(1) : 157-164, March 2009